Analysis of Public Service Quality Improvement Through Bureaucratic Simplification Policies - Elfi Rahmi,; Wijaya, Chandra (Technium Social Sciences Journal, 2022)
This study aims to examine and analyze the implementation of bureaucratic simplification and improve the quality of public services after bureaucratic simplification in Indonesia. In line with community needs development, the demand for public services is also increasing, and this is certainly a challenge for the government to accelerate and improve the quality of public services. Simplification of the bureaucracy is part of implementing bureaucratic reform to realize quality public services and effective and efficient governance so that the bureaucracy becomes dynamic, agile, and professional. This study uses a qualitative method with a literature study. Data were collected from various books, laws and regulations, articles, journals, and electronic data related to the research topic. The results of this study conclude that the simplification of the bureaucracy is still ongoing. The government continues to encourage the implementation of quality public services through the implementation of a comprehensive bureaucratic simplification policy. An increase in the quality of public services after the simplification can be proven by increasing the results of the measurement of the national public service index and the level of compliance of ministries, institutions, and local governments to public services. This can at least be an initial proof that through the spirit of simplifying the bureaucracy, improving the quality of public services can be realized